2013
DOI: 10.3389/fimmu.2013.00260
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DO and Its Role in MHC Class II Antigen Presentation

Abstract: Helper T cells are stimulated to fight infections or diseases upon recognition of peptides from antigens that are processed and presented by the proteins of Major Histocompatibility Complex (MHC) Class II molecules. Degradation of a full protein into small peptide fragments is a lengthy process consisting of many steps and chaperones. Malfunctions during any step of antigen processing could lead to the development of self-reactive T cells or defective immune response to pathogens. Although much has been accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…4A and data not shown). The data on H2-O transcripts drew our attention because DO is known to inhibit the activity of DM, an “editor” needed for dislodging the invariant chain (CD74) derivative, CLIP, and other peptides from the Ag-binding groove of a maturing MHC-II molecule, enabling effective loading of a diverse repertoire of peptides (19, 20). Transcripts encoding both DO chains were expressed at a significantly lower level in perinatal than in adult MECs, independently of Aire (Fig.…”
mentioning
confidence: 99%
“…4A and data not shown). The data on H2-O transcripts drew our attention because DO is known to inhibit the activity of DM, an “editor” needed for dislodging the invariant chain (CD74) derivative, CLIP, and other peptides from the Ag-binding groove of a maturing MHC-II molecule, enabling effective loading of a diverse repertoire of peptides (19, 20). Transcripts encoding both DO chains were expressed at a significantly lower level in perinatal than in adult MECs, independently of Aire (Fig.…”
mentioning
confidence: 99%
“…Hence, the findings were interpreted as DO competing with DM in interaction with DR leading to the inhibition of DM function. While this model has some support in literature [53], kinetic peptide binding and dissociation experiments performed in the presence of DM and/or DO suggested a different mechanism [51,52]. It was reported that DO reduced binding of DR1 to some peptides, and enhanced the binding of some other peptides to DR1.…”
Section: Role Of Hla-do In Immunodominancementioning
confidence: 78%
“…In addition to DM, another non-classical MHC class II accessory molecule, HLA-DO (H2-O in mice), is known to play a role in peptide exchange [5153]. Unlike DM, the expression of HLA-DO or H2-O (DO) is restricted to B cells, thymic medulla and certain subsets of DCs, and its cellular trafficking depends on DM.…”
Section: Role Of Hla-do In Immunodominancementioning
confidence: 99%
“…In Fig 7, the high association of MHC class II antigen presentation , represented by the class II genes including HLA-DM and HLA-DO , reflects the general dominance of HLA-DQ and HLA-DR loci in Fig 2: MHC class II molecules assembled in the ER with the invariant chain (Ii), initially occupying the peptide binding domain, moves into an endosomal compartment and Ii is exchanged with antigenic peptides with the help of HLA-DM and HLA-DO, which down-regulates HLA-DM in B cells [31, 36, 46]. The peptide-MHC class II complex is then displayed on the plasma membrane (Fig 4C).…”
Section: Resultsmentioning
confidence: 99%